The lack of future officers’ methodical competence in physical training as a pedagogical problem - Самокиш, Іван Іванович; Samokish, Ivan; Samokysh, Ivan I.; Самокиш, І. І.; Okhrimenko, Ivan; Коbernyk, Oleksandr; Husarevych, Oleksandr; Krykun, Viktoriia; Kalashnik, Nataliіa; Pavlenko, Vita; Biruk, Nataliia; Butok, Olena; et al. (My University, 2020)
The level of the cadets’ of higher military educational institutions (HMEI), who are future officers, methodical competence in physical training is investigated in the article. 609 cadets participated in the study. Two groups were formed: EG (n=38), which included the cadets who were 3 engaged in various sports and CG (n=65), which included the cadets who were training according to the traditional physical training program. The methodical competence was assessed by the level of mastering the theoretical bases of physical training and the quality of implementation of practical actions of physical training. It was determined that EG cadets had a higher level of methodical competence in physical training than CG cadets at the end of the study at HMEI
The lack of future officers’ methodical competence in physical training as a pedagogical problem / I. Samokysh, I. Okhrimenko, O. Коbernyk, O. Husarevych and others // Revista Dilemas Contemporáneos: Educación, Política y Valores. - Enero 2020, Año VII, Publicación № 2. - 19 р. https://doi.org/10.46377/dilemas.v32i1.1979
Keywords: methodical competence; physical training; sport; cadets; Research Subject Categories::SOCIAL SCIENCES; Research Subject Categories::INTERDISCIPLINARY RESEARCH AREAS::Sports